The effect of alternating shifts on the quality of life and career satisfaction of emergency physicians in Saudi Arabia: A survey study - Najla S Ewain; Anas A Khan (Wolters Kluwer Medknow Publications, 2019)
Background: The Department of Emergency Medicine (EM) provides critical medical care to patients at all times. Providing medical care, especially at night, has led physicians to work in alternating shifts. Objective: The objective of this study was to determine the effect of alternating shifts on the quality of life and career satisfaction among emergency physicians (EP). Design: This was a multicenter, observational, cross-sectional study. Settings: EM departments of major government and private hospitals in Saudi Arabia. Methods: An e-survey-based study using a structured questionnaire was conducted on 234 board-certified EP in 2017. Data were analyzed using the Statistical Package for the Social Sciences software. Results: Most EM physicians (59.4%) were either satisfied or very satisfied in their career, with a majority (39.7%) admitting that shift alternations influenced their job satisfaction. While 52.6% of the physicians denied that shift alternations caused them to think about leaving EM, about 15% admitted that it is a major factor. Approximately, 40.6% of participating physicians believed that shift alternations moderately impacted their social and family life. About 88.1% of physicians believed that one or more medical conditions are primarily caused or aggravated by shift alternations; only 11.9% reported no direct impact on their health. Female physicians; singles; physicians with children, evening shifts, and higher number of shifts; and physicians with less years of experience reported less satisfaction. Physicians with equal distribution of shift times, older age, and more nonclinical hours or with part-time jobs showed more satisfaction. Conclusions: EM physicians report a moderate-to-major negative impact on their social, family, and healthy life due to the constant alternation of shifts. However, the effect did not cause them to think about leaving EM and most of them had high career satisfaction.